Penentuan Harga Jual Pada Seblak Ceu Yani dengan Menghitung Harga Pokok Produksi Menggunakan Metode Full Costing - Azzahra Zalianty; Dwi Setyaningrum; Purwanti Purwanti (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
UKM Seblak Ceu Yani research uses qualitative descriptive methodology. Specifically, by conducting interviews and observations of business actors and collecting financial information such as production costs, fixed costs, and sales figures. The purpose of this study is to use the whole costing approach to analyze production costs in order to determine selling prices. In order to determine selling prices at UKM Seblak Ceu Yani, this study will use the whole costing approach to analyze production costs. The Full Costing method, which accounts for all production costs, including direct labour, raw material costs, and fixed and variable factory overhead expenses, is the methodology employed in this study. The study's findings show that there is a difference in selling prices at UKM Seblak Ceu Yani when the Full Costing approach is used to determine the selling price. This distinction is.